The Use of Psycholinguistic Patterns in Interactive Systems of Active Information Retrieval - Evgenevich Sachkov, Valery; Aleksandrovich Akimov, Dmitry; Aleksandrovich Pavelyev, Sergey (International Journal of Engineering and Technology, 2018)
The article explores the possibility of using psycholinguistic patterns in a dialogue with the Internet visitors. The scheme of the semantic kernel is shown for the purpose-setting installation of the search system and the methodology for constructing patterns, taking into account the psycholinguistic features of constructing a dialogue for obtaining the required information. The model of building psycholinguistic patterns for revealing the semantic information in dialogues is given. Patterns are based on associative links of words and word combinations. Such associative connections allow expanding the list of related words and revealing key information in the best way from short messages. The use of such a method in interactive active search systems makes it possible to improve information exchange and achieve a higher level of identifying the purpose of the dialogue.Â Â Â